Complement receptors regulate differentiation of bone marrow plasma cell precursors expressing transcription factors Blimp-1 and XBP-1. - Gatto, D; Pfister, T; Jegerlehner, A; Martin, S; Kopf, M; Bachmann, M (2005)
Humoral immune responses are thought to be enhanced by complement-mediated recruitment of the CD21-CD19-CD81 coreceptor complex into the B cell antigen receptor (BCR) complex, which lowers the threshold of B cell activation and increases the survival and proliferative capacity of responding B cells. To investigate the role of the CD21-CD35 complement receptors in the generation of B cell memory, we analyzed the response against viral particles derived from the bacteriophage Qbeta in mice deficient in CD21-CD35 (Cr2(-/-)). Despite highly efficient induction of early antibody responses and germinal center (GC) reactions to immunization with Qbeta, Cr2(-/-) mice exhibited impaired antibody persistence paralleled by a strongly reduced development of bone marrow plasma cells. Surprisingly, antigen-specific memory B cells were essentially normal in these mice. In the absence of CD21-mediated costimulation, Qbeta-specific post-GC B cells failed to induce the transcriptional regulators Blimp-1 and XBP-1 driving plasma cell differentiation, and the antiapoptotic protein Bcl-2, which resulted in failure to generate the precursor population of long-lived plasma cells residing in the bone marrow. These results suggest that complement receptors maintain antibody responses by delivery of differentiation and survival signals to precursors of bone marrow plasma cells.